Vittorio Emanuele Orlando e la “questione romana” (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa – 2. Dalle “condizioni svariate e complesse della coscienza giuridica del popolo” alla “sovranità dello Stato” – 3. Il mancato accordo politico – 4. Conclusione.Vittorio Emanuele Orlando and the "Roman question"ABSTRACT: The motivation that leads Orlando to negotiate the solution of the “Roman Question” with Monsignor Bonaventura Cerretti, that he “met” in Paris, as “sent” by Benedict XV, focuses on the work of political agreement, on the “crisis” of the “Orlando ministry” and, therefore, on the Lateran Pacts of 11th February 1929, which mark the overcoming of a politics, founded on the “law of guarantees”, and give a “not very different text from that of Orlando - Cerretti’s one”.